Metabolic engineering of rice endosperm towards higher vitamin B1 accumulation. Issue 6 (11th February 2021) - Strobbe, Simon; Verstraete, Jana; Stove, Christophe; Van Der Straeten, Dominique
Summary: Rice is a major food crop to approximately half of the human population. Unfortunately, the starchy endosperm, which is the remaining portion of the seed after polishing, contains limited amounts of micronutrients. Here, it is shown that this is particularly the case for thiamin (vitamin B1). Therefore, a tissue‐specific metabolic engineering approach was conducted, aimed at enhancing the level of thiamin specifically in the endosperm. To achieve this, three major thiamin biosynthesis genes, THIC, THI1 and TH1, controlled by strong endosperm‐specific promoters, were employed to obtain engineered rice lines. The metabolic engineering approaches included ectopic expression of THIC alone, in combination with THI1 (bigenic) or combined with both THI1 and TH1 (trigenic). Determination of thiamin and thiamin biosynthesis intermediates reveals the impact of the engineering approaches on endosperm thiamin biosynthesis. The results show an increase of thiamin in polished rice up to threefold compared to WT, and stable upon cooking. These findings confirm the potential of metabolic engineering to enhance de novo thiamin biosynthesis in rice endosperm tissue and aid in steering future biofortification endeavours.